FAKTOR-FAKTOR YANG MEMPENGARUHI KECEMASAN MATEMATIKA PADA SISWA SMA - Suminta, Rini Risnawita (2014)
This research aimed to: (1) assessing whether the variable of parental academic support, peer academic support and classroom climate on: mathematics anxiety directly and (2) assessing whether the variable. mathematics self-efficacy and flow mediated parental academic support,peer academic support and classroom climate on mathematics anxiety. The population in this research consists all students of SMA in Kediri,East Java. The sample was as many as study 765 students, taken through multi-stage cluster sampling and simple random sampling method. The data collection techniques used in this research was scales and checklists. There were five types of scales used in the data collection process; (a) the mathematics anxiety scale, (b) the academic support scale, (c) the classroom climate scale, (d) the mathematics self-efficacy scale and (e) the flow scale. The data were analyzed using Structural Equation Models (SEM). The research resulted: (1) the variable of parental academic support was not influence directly on mathematics anxiety, peer academic support was positive influence directly on mathematics anxiety and classroom climate was negative influence directly on mathematics anxiety, and (2) the variable mathematics selfefficacy and flow were mediated parental academic support, peer academic support and classroom climate on mathematics anxiety. Key words: Mathematics Anxiety, Academic Support, Classroom Climate, Mathematics Self-Efficacy, And Flow.